Hockey sticks, purple smoke bombs, and empathy: female character representation in Pakistani comics. Issue 1 (2nd January 2023) - Aayeshah, Wajeehah
ABSTRACT: This paper explores representations of strong, empowered female characters in contemporary Pakistani comics. Recently, comics have been generating narratives that can create awareness of gender (in)equality and female empowerment in Pakistan. This paper explores the female characters in three Pakistani comics: Raat, Passban- the Guardian and Team Muhafiz. All analysis and discussion offered will be based on the comics and interviews with their respective creative team. This paper will argue that contemporary Pakistani female comic characters challenge the existing socio-political hierarchy through activism and vigilantism. This paper posits that a major reason the comics succeed in their mission is due to being instantly recognisable to its intended audience by being deeply rooted, visually and narratively, in Pakistani culture. The aim of this paper is to contribute to bridging of the existing gap in the discourse about Pakistani female representation in Comic Studies.